Is a Contractual Clause Excluding a Right of Set-Off Subject to the Requirement of Reasonableness in the Unfair Contract Terms Act? - GOH, Yihan (Institutional Knowledge at Singapore Management University, 2015)
The Court of Appeal in Koh Lin Yee v Terrestrial Pte Ltd [2015] SGCA 6 (“Koh Lin Yee”) has decided that a contractual clause excluding a right of set-off is subject to the requirement of reasonableness in the Unfair Contract Terms Act (Cap 396, 1994 Rev Ed) (“UCTA”). In doing so, it also laid down some general guiding principles relating to the application of the UCTA, namely, when a party is considered to be dealing “as consumer” under s 12(1), when a contract contains standard terms of business under s 3(1) and the application of the requirement of reasonableness.